DETERMINAN POTENSI KECURANGAN LAPORAN KEUANGAN DI INDONESIA - Hairani, Yuniar Is; Isnawati, Isnawati (Jurnal Riset Akuntansi, 2024)
This investigation is based on a case of fraud in a company like the one that has occurred in PT Kimia Farma Tbk and PT Indofarma Tbk. This is intended to make a test the variables of the cause of fraud in detecting the potential for fraud occurrence in manufacture companies listed on the Indonesian Stock Exchange by 2020-2022 which refers to the fraud hexagon theory. The study proposes six hypotheses tested with the f-score model. This research using second data obtained from the company's annual statement of accounting by 2020-2022, which is further analyzed using variables in the fraud hexagon theory. The results showed that the external pressure calculated with DAR influenced the potential for fraudulent financial reporting, when the External Auditor Quality, Auditor Change,, Changes in Director, and Government Projects calculated using dummy variables and CEO’s Picture calculated based on the number of corporate leaders’ photos did not influence the potential of financial fraud reports.